Prevalence of mental disorders and high rates of absenteeism from work among healthcare professionals in Slovenia: a retrospective study - Darja Korošec; Dominika Vrbnjak; Gregor Štiglic (BMJ Open)
Objectives To investigate the prevalence of mental disorders and the higher rates of absenteeism from work among healthcare workers employed in Slovenia by analysing the prevalence of sick leave and medication prescriptions for treatment of mental health and behavioural disorders from 2015 to 2020.Design Retrospective analysis of nationwide data on absenteeism and prescription of medications for treatment of mental health and behavioural disorders (anxiolytics, antipsychotics, antidepressants).Setting National databases of the National Institute of Public Health in Slovenia.Participants All employed healthcare workers (35 008 in December 2020): dentists, midwives, nurses, nursing assistants, pharmacists and physicians in Slovenia from 2015 to 2020.Results The most time spent on sick leave by male healthcare workers aged >50 was for ‘neoplasms’ (71.50 days on average), followed by ‘mental health and behavioural disorders’ (62.08 days on average). Female healthcare workers under 40 years old spent the most time on sick leave for ‘pregnancy, childbirth, and the postpartum period (puerperium)’, causing an average of 58.38 days of sick leave. From 2015 to 2020, the highest increase in prescribed medications for treatment of mental health and behavioural disorders was among nursing assistants (an increase of 38.42%), pharmacists (an increase of 29.36%) and nurses (an increase of 26.61%); since the COVID-19 pandemic, an increase of 12.36% was found among dentists, an increase of 11.51% among pharmacists and an increase of 11.36% among nurses.Conclusion The prescription of medications for treatment of mental health and behavioural disorders was on the rise from 2015 to 2020. The importance of employee health to individuals and society necessitates the systematisation of effective prevention programmes as well as programmes to assist those in need, especially health workers, whose work contributes significantly to maintaining public health.